Human impact and vegetation change as triggers for sediment dynamics in the river Rhine catchment - Dix, Andreas; Burggraaff, Peter; Kleefeld, Klaus-Dieter; Küster, Hansjörg; Schirmer, Wolfgang; Zimmermann, Andreas (ERDKUNDE, 2005)
The main goal of the international LUCIFS project is to analyse the human impact on the hydrological dynamics of the river and the sediment budget. The main thesis is, that earlier human societies shaped the fluvial system and the sediment transport in a fundamental way since the beginning of agriculture. The River Rhine can be seen as a typical river, which is shaped by humankind over a very long period. This paper gives an overview over the current knowledge and research situation. In a first chapter several major steps of a growing human impact on fluvial dynamics will be identified in the sediment archives and the pollen profiles, which contain information of the vegetation change. In case of the Stone Age and the period from the medieval age onwards the aim is to look for other sources like archaeological remains or archival sources. The main thesis is, that the human impact became more and more important throughout this period and especially during the last 300 years.